Generalized Hyperpigmentation in Graves' Disease: A Case Report - Shah, S; Shakya, S; Shakya, A; Bhari, R (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Hyperpigmentation is rarely described as a clinical feature of hyperthyroidism, however, it is one of the rare cutaneous manifestations of Graves' Disease. There are few reported cases of Grave's disease with diffuse hyperpigmentation. We hereby describe a rare case with diffuse hyperpigmentation induced by Graves' disease. Case: A 29-year-old woman came with the complaints of generalized hyperpigmentation of body since the past 3 months. On examination, hyperpigmentation was observed throughout the whole body, especially on the face, neck and the extremities. Conclusion: The pathophysiological mechanism is not well elucidated. It has been hypothesized that thyrotoxicosis is associated with an increased ACTH release causing overproduction of melanin and that melanocytes express TSH receptors resulting in their proliferation when stimulated with TRAb. More studies are needed to understand the relationship between skin color modification and thyroid function status.